RHETORICAL PATTERN IN ARGUMENTATIVE ESSAY WRITING BY EFL STUDENTS OF IAIN SURAKARTA - Sujito Sujito; Wildan Mahir Muttaqien (Center of Language and Cultural Studies, 2016)
This study reports pattern of rhetoric in argumentative essay of academic writing accros three achievement categories: fast learner, medium learner, and slow learner. Descriptive correlation between the pattern of the rhetoric and overall quality of academic writing was also identified. This research was descriptive study using content analysis approach. The research subjects were 3 classes of semester VII EFL student out of 9 classes selected in purposive sampling. Pattern of rhetoric in students work was analyzed in seven categories: thesis statement, reservation, background information, rational appeal, affective appeal, conclusion, and hesitation. ESL composition profile by Jacobs was employed to measure students’ academic argumentative essay. The finding showed that rhetoric pattern categories in three different writing achievers was failed to use. However, strong connectivity between pattern of the seven rhetoric categories and overall quality of academic writing across level of achievement was significantly linked.